The Changing Perception of Communication Needs—A Litmus Test for the Warnock Legacy - Law, James (Frontiers in Education, 2019)
Meeting Lady Warnock1 at the final conference for some work commissioned by the DfEE/NHS in 2001, she said that one of her greatest concerns about her earlier report is the fetishisation of the statement of education needs. It was, of course, true that with the “statement,” as it came to be known, was often equated with her report, and triggered a rather legalistic culture with all the accompanying processes of tribunals and appeals. Nowhere was this more apparent than in the “border disputes” between health and education as to who was responsible for children with speech, language and communication needs (SLCN), a term which only emerged 25 years after her report was published. In this paper it is argued that the nature of disability has changed since Warnock. Communication disability is now one of the most disabling conditions and communication access at least as important as physical access. It is argued that communication should perhaps be seen as a litmus test2 for whether the integration of children with support needs in the classroom is achievable. Although Warnock resisted diagnostic labels in favor of “needs” there has been a burgeoning market in measures of cognition, language and behavior since the 1970s. The paper goes on to look at the ways that the term SLCN has played out across health and educational services and ends up comparing the recommendations in the original report with those in the recent (2018) Bercow - 10 Years On report.